2022
DOI: 10.1007/s00426-022-01773-w
|View full text |Cite
|
Sign up to set email alerts
|

Why motor imagery is not really motoric: towards a re-conceptualization in terms of effect-based action control

Abstract: Overt and imagined action seem inextricably linked. Both have similar timing, activate shared brain circuits, and motor imagery influences overt action and vice versa. Motor imagery is, therefore, often assumed to recruit the same motor processes that govern action execution, and which allow one to play through or simulate actions offline. Here, we advance a very different conceptualization. Accordingly, the links between imagery and overt action do not arise because action imagery is intrinsically motoric, bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(4 citation statements)
references
References 158 publications
0
4
0
Order By: Relevance
“…Previous research found that both MIP and OAP have shown a greater hand-learning process than a placebo [12,13]. Several hypotheses have been proposed [14], but it seems that processes of MRS share certain cerebral representations, along with processes of preparation for and real motor execution, suggesting that every action we execute is planned, initiated, and controlled through an imagery-like process [15,16]. Neuroimaging studies have revealed that, during MRS, there is a neurophysiological activation of the brain areas involved in the planning and execution of voluntary movement (primary motor cortex, supplementary motor area, cerebellum, premotor area, the inferior and superior parietal lobule, and the basal ganglia) similar to what happens when the movement is actually performed [17,18].…”
Section: Introductionmentioning
confidence: 98%
“…Previous research found that both MIP and OAP have shown a greater hand-learning process than a placebo [12,13]. Several hypotheses have been proposed [14], but it seems that processes of MRS share certain cerebral representations, along with processes of preparation for and real motor execution, suggesting that every action we execute is planned, initiated, and controlled through an imagery-like process [15,16]. Neuroimaging studies have revealed that, during MRS, there is a neurophysiological activation of the brain areas involved in the planning and execution of voluntary movement (primary motor cortex, supplementary motor area, cerebellum, premotor area, the inferior and superior parietal lobule, and the basal ganglia) similar to what happens when the movement is actually performed [17,18].…”
Section: Introductionmentioning
confidence: 98%
“…Previous research has postulated at least three (non-exclusive) potential inhibitory mechanisms that might operate during motor imagery (Guillot, Di Rienzo, et al, 2012). First, the need to prevent execution could be integrated within the representation of the action to be produced internally so that only "subthreshold" motor commands are involved during motor imagery (see also Bach et al, 2022;Glover et al, 2020). Second, motor inhibition could be applied broadly to all ongoing actions and to all effectors involved in these actions (global motor inhibition).…”
Section: Introductionmentioning
confidence: 99%
“…AOMI could be an important tool for enhancing jumping performance because the nature of the jumping movement requires the interaction of both visual and kinesthetic elements ( Wright et al, 2022 ). AOMI can support the formation of mental representations of the jumping movement by observing the correct form and technique of the jump ( Eaves et al, 2016a ; Kim et al, 2017 ; Bach et al, 2022 ). This method can enhance movement performance by increasing brain activation of the muscle groups actively used during jumping.…”
Section: Introductionmentioning
confidence: 99%